The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fneur.2020.00293
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Steno-Occlusive Middle Cerebral Artery and Basal Ganglia Perivascular Spaces

Abstract: Objectives: Enlarged perivascular spaces in the basal ganglia (BG-EPVS) share common vascular risk factors with atherosclerosis. However, little is known about the relationship between steno-occlusive middle cerebral artery (MCA) and BG-EPVS. In this cross-sectional study, we aimed to test the hypothesis that severe MCA stenosis or occlusion is associated with increased MRI-visible BG-EPVS. Methods: We retrospectively reviewed 112 patients with a steno-occlusive MCA from Fujian Medical University Union Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…For instance, basal ganglia ePVS are independently related to nonimaging measures of arterial stiffness, 17,18 hypertensive arteriopathy, 19,40 and atherosclerosis. 41 Localization of such findings to the basal ganglia may be in part a result of an increased susceptibility to the early effects of cSVD in the perforating arterioles that supply the basal ganglia. 4,42 Our results further suggest that rates of ePVS development may differ as a function of brain region.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, basal ganglia ePVS are independently related to nonimaging measures of arterial stiffness, 17,18 hypertensive arteriopathy, 19,40 and atherosclerosis. 41 Localization of such findings to the basal ganglia may be in part a result of an increased susceptibility to the early effects of cSVD in the perforating arterioles that supply the basal ganglia. 4,42 Our results further suggest that rates of ePVS development may differ as a function of brain region.…”
Section: Discussionmentioning
confidence: 99%
“…Standardized parameters for the MRI sequences are as follows: T1WI sequence: repetition time (TR), 1,990 ms; echo time (TE), 8.7 ms, field of view (FOV), 230 × 217 mm 2 ; T2WI sequence: TR, 4,700 ms; TE, 109 ms; FOV, 230 × 217 mm 2 ; fluid-attenuated inversion recovery (FLAIR) sequence: TR, 9,000 ms; TE, 95 ms; FOV, 230 × 217 mm 2 ; diffusion-weighted imaging (DWI) sequence: TR, 3,570 ms; TE, 67 ms; FOV, 235 × 235 mm 2 . We determined well-established baseline imaging cSVD markers according to the previously published method ( Wardlaw et al, 2013 ; Capuana et al, 2020 ; Du et al, 2020a ). Lacunes of presumed vascular origin were round or oval, located in the subcortex, similar to the signal of cerebrospinal fluid between 3 and 15 mm in diameter at fluid-attenuated inversion recovery (T2-FLAIR) and usually with low intensity of central cerebrospinal fluid and high-intensity margin around it ( Wardlaw et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…CMBs were a round or oval low-signal intensity focus of cerebral parenchyma on T2-weighted gradient-recalled echo (T2*-GRE) or susceptibility-weighted imaging (SWI) with a diameter of 2–10 mm ( Wardlaw et al, 2013 ; Capuana et al, 2020 ). Enlarged perivascular spaces at basal ganglia (BG-EPVS) and centrum semiovale (CSO-EPVS) were defined on T2-weighted using a validated five-point ordinal scale as follows: 0 = no EPVS, 1 = 1–10 EPVS, 2 = 11–20 EPVS, 3 = 21–40 EPVS, and 4 = > 40 EPVS ( Wardlaw et al, 2013 ; Du et al, 2020a ). We graded WMH in periventricular and deep white matter on T2-FLAIR sequences according to the Fazekas criteria ( Staals et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…5 Recently, studies have shown that chronic SVD burden exists in ischemic stroke patients with LAD, especially ICAS. 6,7 Only a few studies have evaluated the relationship between different SVD imaging markers and the degree of ICAS. 8,9 Although the imaging markers of SVD, such as WMH, PVS, CMB, and chronic lacunes, are correlated to some extent, they might have different etiologies.…”
mentioning
confidence: 99%
“…According to the STandards for ReportIng Vascular changes on nEuroimaging (STRIVE) criteria, the imaging markers of SVD usually include white matter hyperintensity (WMH), perivascular space (PVS), chronic lacunes, cerebral microbleeds (CMBs), recent small subcortical infarcts, and brain atrophy 5 . Recently, studies have shown that chronic SVD burden exists in ischemic stroke patients with LAD, especially ICAS 6,7 . Only a few studies have evaluated the relationship between different SVD imaging markers and the degree of ICAS 8,9 …”
mentioning
confidence: 99%